2013
DOI: 10.1177/0143034313479698
|View full text |Cite
|
Sign up to set email alerts
|

Do cyberbullies suffer too? Cyberbullies’ perceptions of the harm they cause to others and to their own mental health

Abstract: While it is recognized that there are serious sequelae for students who are victims of cyberbullying including depression, anxiety, lower self-esteem and social difficulties, there has been little research attention paid to the mental health of students who cyberbully. It is known that students who traditionally bully report they feel indifferent to their victims, showing a lack of empathy and that they themselves are at increased risk for psychosocial adjustment. However, there is scant research on the mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
98
1
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 72 publications
10
98
1
17
Order By: Relevance
“…Similar to previous studies (e.g., Campbell et al 2013;Hughes et al 2009), females perceived TB and CB to be more harmful than males. Furthermore, in general, participants found TB to be more harmful than CB, and as expected, victims perceived bullying more hurtful than perpetrators.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to previous studies (e.g., Campbell et al 2013;Hughes et al 2009), females perceived TB and CB to be more harmful than males. Furthermore, in general, participants found TB to be more harmful than CB, and as expected, victims perceived bullying more hurtful than perpetrators.…”
Section: Discussionsupporting
confidence: 87%
“…Most previous studies found that females are more likely to be a CB victim than males (e.g., DeHue et al 2008;Ortega et al 2009), while the reverse has been observed among TB victims (e.g., Huang and Chou 2010;Wang et al 2009). Campbell et al (2013) also reported of a higher proportion of female TB victims in their study and interpreted these higher rates as a possible consequence of using TB forms in the assessment that highly reflect indirect forms of aggression (e.g., exclusion) which are more prevalent among females (Hara 2002). The definition participants read of TB (Shaw et al 2013) in the present study also contained a considerable proportion of indirect forms of aggression (e.g., spreading rumors, not allowing someone to join in an activity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviours consistently identified as cyberbullying include: threatening or nasty emails, mobile texts or Internet postings; social exclusion from the online community; impersonating another person or forwarding on the cyber victim's private information; posting derogatory or embarrassing pictures or videos; creating websites designed to hurt, intimidate or degrade victims; trolling or stalking; and harassing others in virtual environments or online games [2,10,[17][18][19].…”
mentioning
confidence: 99%
“…Akár a felnőttkorra is kihathatnak, a fiúk esetében a gyakori zaklatásnak való kitettség a későbbi évek során a szorongásos zavarok megjelenéséhez vezethet (Copeland, Wolke, Angold és Costello, 2013), illetve a cyberbullying a szociális zavarok és depresszió kialakulását is okozhatja (Campbell, Slee, Spears, Butler és Kift, 2013;Landoll, La Greca, Lai, Chan és Herge, 2015 …”
Section: Az Internetes Zaklatás Következményeiunclassified